Can Sense of Opportunity Identification Efficacy Play a Mediating Role? Relationship Between Network Embeddedness and Social Entrepreneurial Intention of University Students - Wang, Wenke; Tang, Yingkai; Liu, Yao; Zheng, Tao; Liu, Jing; Liu, Haiyue (Frontiers in Psychology, 2019)
Social entrepreneurship is an entrepreneurial activity centering on solving social problems and creating social values, which can effectively alleviate the problems of sustainable development such as an excessive gap between the rich and the poor, a lack of resources and so on, and can resolve the "triple failures" of government, the market and public welfare departments to a certain extent. As the subjective attitude of entrepreneurs, entrepreneurial intention can predict a representational incidence rate of entrepreneurial behavior. Therefore, aimed at university students, a special group of entrepreneurs, this paper constructs a theoretical framework of "network embeddedness - sense of opportunity identification efficacy - university students' social entrepreneurial intention" from the perspective of social cognitive theory through 466 pieces of valid survey data, and uses Stata.14 to construct a multiple linear regression model to explore the mechanism of action between the three. The results show that university students' sense of opportunity identification efficacy can significantly and positively stimulate their social entrepreneurial intention, and the network embeddedness (network scale and network intensity) of entrepreneurs is also significantly and positively correlated with their sense of opportunity identification efficacy; however, via the hierarchical regression model, it was found that the sense of opportunity identification efficacy can only partially mediate the relationship between network embeddedness and university students' social entrepreneurial intention, which is mainly manifested in the positive correlation between university students' social entrepreneurial intention and their network scale, and is unrelated to network intensity. This research contributes to enriching the theory of social entrepreneurial intention and guides the strengthening of university students' social entrepreneurial intention in reality.